1993
DOI: 10.1016/0092-8674(93)90273-s
|View full text |Cite
|
Sign up to set email alerts
|

Spatially localized rhomboid is required for establishment of the dorsal-ventral axis in Drosophila oogenesis

Abstract: The establishment of dorsal-ventral asymmetry of the Drosophila embryo requires a group of genes that act maternally. None of the previously identified dorsal-ventral axis genes are known to produce asymmetrically localized gene products during oogenesis. We show that rhomboid (rho), a novel member of this group, encodes a protein that is localized on the apical surface of the dorsal-anterior follicle cells surrounding the oocyte. Loss of rho function causes ventralization of the eggshell and the embryo, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 51 publications
3
99
0
1
Order By: Relevance
“…3). Similar eggshell defects have been described for grk, top/DER, cni, rho, and brn mutations, which block dorsal follicle cell fate determination and produce eggshells referred to as ventralized (Schiipbach 1987;Ashburner et al 1990;Goode et al 1992;Ruohola-Baker et al 1993). As shown in Table 2, 23% of the eggs produced by orh""^^Iorh""^^ females displayed fused dorsal appendages and 6% lacked both dorsal appendages.…”
Section: Orb™^* Eggs Display D/v Defectsmentioning
confidence: 84%
See 2 more Smart Citations
“…3). Similar eggshell defects have been described for grk, top/DER, cni, rho, and brn mutations, which block dorsal follicle cell fate determination and produce eggshells referred to as ventralized (Schiipbach 1987;Ashburner et al 1990;Goode et al 1992;Ruohola-Baker et al 1993). As shown in Table 2, 23% of the eggs produced by orh""^^Iorh""^^ females displayed fused dorsal appendages and 6% lacked both dorsal appendages.…”
Section: Orb™^* Eggs Display D/v Defectsmentioning
confidence: 84%
“…Since this phenotype suggests that too many follicle cells receive a dorsalizing signal, these genes may act to restrict the expression of the signal temporally and/or spatially. The opposite phenotype is produced by gurken {grk), torpedo [top/DER], coinichon [cni], rhomboid (rho), and brainiac [brn] mutations, which cause cells that normally develop as dorsal to adopt a ventral fate on the eggshell (Schiipbach 1987;Ashbumer et al 1990;Goode et al 1992;Ruohola-Baker et al 1993). The embryos within grk, top/DER, cni, and rho eggs are ventralized as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Grk-Egfr signaling process that is required for dorsoventral patterning, is believed to take place during stage 9, after the oocyte nucleus has moved to its dorsal-anterior position during stage 8 (Montell et al 1991). Early response genes in the follicle cells, such as kek-1 and rhomboid, begin to show a dorsoventral asymmetry in their expression pattern beginning at stage 9 of oogenesis (Ruohola-Baker et al 1993;Musacchio and Perrimon 1996). The gene nudel has also been shown to be expressed during stage 10 of oogenesis (Hong and Hashimoto 1995).…”
Section: Expression Of Wind In the Follicle Cells Occurs When The Dormentioning
confidence: 99%
“…2) (Freeman 2009). First identified in flies, genetic analysis showed that rhomboid-1 was involved in EGFR signaling but its precise role was obscure (Ruohola-Baker et al 1993;Sturtevant et al 1993;Freeman 1994). Genetic mosaic experiments indicated that it acted in the signal-emitting cell, rather than the EGFRexpressing cell, implying a role in signal generation (Wasserman et al 2000).…”
Section: Regulation Of Egfr Signaling In Drosophila By Ligand Proteolmentioning
confidence: 99%